A High Frequency of Peripheral Blood IL‐22+CD4+ T Cells in Patients With New Onset Type 2 Diabetes Mellitus. Issue 2 (25th November 2014) - Guo, Hui; Xu, Bing‐Chuan; Yang, Xi‐Ge; Peng, Di; Wang, Ye; Liu, Xiao‐Bo; Cui, Cheng‐Ri; Jiang, Yan‐Fang
Abstract : Background: This study is aimed at investigating the frequency of different functional IL‐22 + CD4 + T cells in Chinese patients with type 2 diabetes mellitus (T2DM). Methods: The frequency of circulating IFN‐γ+IL‐17‐IL‐22‐CD4 + (Th1), IFN‐γ‐IL‐17A+IL‐22‐CD4 + (Th17), and IFN‐γ‐IL‐17A‐IL‐22 + CD4 + (Th22), and other subsets of IL‐22 + CD4 + T cells in 31 patients with new onset T2DM and 16 healthy controls was characterized by flow cytometry. The levels of serum IL‐22, IL‐17, IFN‐γ, insulin C‐peptide, hemoglobin A1c (HbA1c), fasting plasma glucose, and insulin were examined. Results: The frequency of Th1, Th17, Th22, IFN‐γ + IL‐17 − IL‐22 +, and IFN‐γ − IL‐17 + IL‐22 + CD4 + T cells and the concentrations of IL‐22, but not IL‐17 and IFNγ, in the patients were significantly higher than controls. The percentages of Th22 cells were correlated positively with the frequency of IFN‐γ − IL‐17 + IL‐22 + CD4 + T cells, the values of body mass index (BMI) and homeostatic model assessment insulin resistance (HOMA‐IR), and the levels of serum IL‐22 in those patients. Conclusion: Our data suggest that IL‐22 + CD4 + T cells may contribute to the early process of T2DM.